Association of Tumor Microenvironment T-Cell Repertoire and Mutational Load With Clinical Outcome After Sequential Checkpoint Blockade in Melanoma - Yusko, Erik (Cancer Immunol Res, 2019)
To understand prognostic factors for outcome between differentially sequenced nivolumab and ipilimumab in a randomized phase II trial, we measured T-cell infiltration and PD-L1 by immunohistochemistry, T-cell repertoire metrics, and mutational load within the tumor. We used next-generation sequencing (NGS) and assessed the association of those parameters with response and overall survival. Immunosequencing of the T-cell receptor β-chain locus (TCRβ) from DNA of 91 pretreatment tumor samples and an additional 22 pairs of matched pre- and post-treatment samples from patients who received nivolumab followed by ipilimumab (nivo/ipi), or the reverse (ipi/nivo), was performed to measure T-cell clonality and fraction. Mutational and neoantigen load were also assessed by NGS in 82 of the 91 patients. Tumors were stained using immunohistochemistry for PD-L1(+) and CD8(+) T cells. Pretreatment tumor TCR clonality and neoantigen load were marginally associated with best response with nivo/ipi (P = 0.04 and 0.05, respectively), but not with ipi/nivo. Amalgamated pretreatment mutational load and tumor T-cell fraction were significantly associated with best response with nivo/ipi (P = .002). Pretreatment PD-L1 staining intensity and CD8(+) T-cell counts were correlated with T-cell fraction and clonality, but not mutational or neoantigen load. Patients with increased T-cell fraction post-treatment at week 13 had a 30-fold increased likelihood of survival (P = .002). Mutational and neoantigen load, and T-cell infiltrate within the tumor, were associated with outcome of sequential checkpoint inhibition using nivolumab then ipilimumab, but not when ipilimumab was administered before nivolumab.